EXAMINATION OF 261 AVULSED TEETH FROM PATIENTS TREATED IN EMERGENCY DENTAL SERVICE (CIPEEX, 2025)
This study analyzes 261 cases of avulsed permanent teeth treated in a dental emergency service. It aims to evaluate the prevalence, treatment protocols, and outcomes of tooth avulsion in urgent care. Using a retrospective approach, patient records were reviewed to assess demographic factors, causes of avulsion, immediate management, and long-term outcomes. Findings reveal that factors such as time between avulsion and treatment, storage media, and initial management affect replantation success. Timely intervention and proper storage significantly improve the chances of successful tooth retention. This study highlights the importance of prompt and effective management for preserving avulsed teeth and offers insights for dental professionals.
Keywords: Dental trauma; oral epidemiology; tooth avulsion; tooth replantation